The Personal Wellbeing Index in Spanish Palliative Care Professionals: A Cross-Sectional Study of Wellbeing - Pérez-Belmonte, Sergio; Galiana, Laura; Fernández, Irene; Vidal-Blanco, Gabriel; Sansó, Noemí (Frontiers in Psychology, 2021)
Health professionals are especially exposed to stress, with consequences on professionals’ health and wellbeing. However, palliative care professionals’ wellbeing has been the subject of very little research. The aim of this work is to study the Personal Wellbeing Index in a sample of Spanish palliative care professionals, as well as to study their levels of wellbeing and the relationships of wellbeing with variables such as gender, age, marital status, profession, and professional quality of life. A cross-sectional survey of Spanish palliative care professionals was conducted. The Spanish version of the Personal Wellbeing Index and the Short version of the Professional Quality of Life scale were used. 296 palliative care professionals attending patients at the end of life participated in the study. They showed medium to high levels of wellbeing. The PWI showed an adequate internal structure (χ2(20)=116.130 (p<.001); CFI=.970; SRMR=.041; RMSEA=.140[.116,.166]) and excellent estimates of reliability (α=.879 and CRI=.923). Wellbeing was higher for married compared to single, and showed no relation with age, gender, and profession. Additionally, a structural equation model was estimated, in which a positive relation was found between wellbeing and compassion satisfaction, and a negative one with burnout. The PWI is adequate to measure personal wellbeing in Spanish palliative care professionals.